ANALISIS PERSENTASE INDEKS KADAR CPO (CRUDE PALM OIL) DI PTPN III AEK NABARA KECAMATAN BILAH HULU - Yusmaidar Sepriani (UNIVERSITAS LABUHANBATU, 2019)
Percentage analysis of CPO (Crude Palm Oil) index in PKS PTPN III Aek Nabara Selatan Kecamatan Bilah upstream. The results of this study by presenting the data using IBM SPSS 20.0 can be concluded the results of multiple linear regression calculation declared the amount of CPO production to the influence of free fatty acids, water content, impurity content in PKS PTPN III Aek Nabara Selatan Kecamatan Bilah Hulu. This shows the results of a strong and positiveget value of 0.8 close to 1 it means to have the effect of the amount of CPO production in PKS PTPN III Kebun Aek Nabara Selatan with the value of R-Square 0.008 can be interpreted that the influence of Fatty Acids Free, Water Content, Impurities concentration to the production amount of 8% (0.8) while the remaining 98.2% is influenced by other models not included in the test. Keywords : CPO, impurity level, water content